(untitled) (Altre Modernità, 2020)
Matteo Loconsole, Educazione e sessualità. Gli almanacchi di Paolo Mantegazza (1866-1905) (Milano, Unicopli, 2019, 148 pp. ISBN 978-884-002-106-5) di Edwige Comoy Fusaro